Application of a Hybrid Approach Using PCA based TOPSIS Method for Multi Objective Optimization of EDM Process Parameters During Machining of H11 Die Steel Using P/M Processed Metal Matrix Composite - Pallavi Senapati, N.; Tripathy, S. (International Journal of Engineering and Technology, 2018)
Metal matrix composites (MMC) are found to have many applications in the space and aviation industries. This paper presents the details of a comparative study made on the machinability of H11 die steel by electric discharge machining (EDM) process using copper and powder metallurgy (P/M) processed Cu-Cr MMC as the tool.  Taguchi method was used for the experimental design and experiments were conducted using L9 orthogonal array for each tool. The present work investigates the influence of machining parameters such as peak current (Ip), pulse on time (Ton), duty cycle (DC) and gap voltage (Vg) on material removal rate (MRR), tool wear rate (TWR), diametral overcut (DOC) and surface roughness (SR). Cu-Cr composite tool demonstrates better performance than copper tool.  Multi-objective optimization was performed using a combination of principal component analysis (PCA) with technique for order of preference by similarity to ideal solution (TOPSIS) to achieve the optimum parameter setting for copper and Cu-Cr tool. The optimal results obtained for copper tool was at Ip=3A, Ton=150µs, DC=80%, Vg=40V and for Cu-Cr tool was at Ip=3A, Ton=200µs, DC=90%, Vg=50V.